Theory of Planned Behavior on The Psycho-Social Determinants of Drug Use Among Adolescents in Samarinda, East Kalimantan - Syukma Rhamadani Faizal Nur; Bhisma Murti; Pawito . (Journal of Health Promotion and Behavior, 2017)
Background: Drug abuse is serious global health problem. Drug users aged 10-59 years in Indonesia has been increasing steadily. According to data from National Board for Drug Abuse (Badan Narkotika Nasional, BNN), the prevalence of drug users in East Kalimantan was 59,195 (3.07%) of population aged 10-59 years of 1,930,936 people. This study aimed to investigate the psycho-social determinants of drug use among adolescents in Samarinda, East Kalimantan, using Theory of Planned Behavior.Subjects and Method: This was an analytical observational study with cross-sectional design. The study was carried out at Badan Rehabilitasi Tanah Merah, Samarinda, East Kalimantan, from July to August, 2017. A sample of 150 adolescents were selected for this study by fixed disease sampling, including 50 adolescent drug users, and 100 adolescent non drug users. The dependent variable was drug use. The independent variables were intention, attitude, subjective norm, perceived behavior control, peer group, parenting style, and family harmony. The data were collected by pre-tested questionnaire and analyzed using path analysis.Results: Drug use was directly determined by strong intention (b= 2.18; 95% CI= 1.22 to 3.14; p<0.001), negative attitude (b= 1.79; 95% CI= 0.76 to 2.82; p=0.001), low subjective norm (b= 1.13; 95% CI= 0.09 to 2.17; p= 0.034), and weak perceived behavior control (b= 2.83; 95% CI= 1.48 to 4.19; p<0.001). Intention was determined by weak perceived behavior control (b= 1.18; 95% CI = 0.14 to 2.22; p<0.001). Subjective norm was determined by family harmony (b= 2.03; 95% CI= 0.96 to 3.09; p<0.001), authoritarian parenting style (b= 1.25; 95% CI= 0.15 to 2.36; p=0.026), and peer group (b= 1.46; 95% CI= 0.37 to 2.54; p=0.009).Conclusion: Drug use is directly determined by intention, attitude, subjective norm, and perceived behavior control. Family harmony, authoritarian parenting style, and peer group affect drug use indirectly.Keywords: drug use, Theory of Planned Behavior, path analysisCorrespondence: Syukma Rhamadani Faizal Nur. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami No.36 A, Surakarta 57126, Central Java, Indonesia. Email: faizalrhamadani@gmail.com. Mobile: +6281253121828.Journal of Health Promotion and Behavior (2017), 2(3): 272-281https://doi.org/10.26911/thejhpb.2017.02.03.07